Legislating for equality : a multinational collection of non-discrimination norms. - Naʻamat, Talia; Osin, Nina; Porat, Dina (Martinus Nijhoff Publishers, 2013)
In this second volume we turn our attention to the Americas: North America, Latin America, and the Caribbean. During the past decade many American countries amended their constitutions and enacted laws protecting the rights of Indigenous people.